Corrosion Behavior of Equiatomic Bio-High Entropy Alloys CoCrMoMnNb Fabricated in Multiple Remelting Processes - Rokhmanto, Fendy; Erryani, Aprilia; Setyawan, Albertus Deny Heri; Thaha, Yudi Nugraha; Zakiyuddin, Ahmad; Kartika, Ika; Harjanto, Sri (Metalurgi, 2024)
High-entropy alloys are described as equiatomic alloys of more than five elements or materials with five or more element constituents with a high mixing entropy (ΔSmix ≥ 1.5R), where the composition of the element is 5–35%, respectively. One application of HEA (high entropy alloys) materials is in the orthopedic field, where they are developed as biomaterials. Behavior, the correlation between the elemental distribution, and the microstructure of the material were investigated during multiple remelting processes known as Bio-HEAs. The development of Bio-HEAs is exciting in terms of design material, fabrication, and their properties. In this paper, the corrosion behavior and the correlation of the elemental distribution and the microstructure of the material were investigated during the multiple remelting process. The equiatomic CoCrMoMnNb was prepared in vacuum arc melting under an argon atmosphere and melted in a water-cooled copper mold. The total amount of ingot was approximately 25 grams, then flipped and remelted several times, 4, 8, and 12 cycles. The final composition of the alloys was confirmed by EDX (energy dispersive x-ray spectroscopy). The microstructure was investigated with an optical microscope and the SEM (scanning electron microscope). The corrosion parameter occurred in Hank’s solution at 37°C, at a scan rate of 1 mV/s. The CCM-MnNb fabricated with 8 cycles of the remelting process exhibits the lowest corrosion rate (0.0038 mmpy) and donor densities (2.67 × 10¹⁹ cm⁻³), while the charge transfer resistance number is the highest (18250.94 Ω cm⁻²). The outstanding corrosion resistance of the alloys is induced by the presence of the finer dendrites and the chromium oxide (Cr₂O₃) protective layer on the alloy's surface.